Pre-harvest foliar application of calcium chloride improves berry quality and storage life of table grape cvs. ‘perlette’ and ‘kings’s ruby’ - Abbasi, Nadeem Akhtar; Shafique, Muhammad; Ali, Irfan; Qureshi, Abdul Ahad; Hafiz, shfaq Ahmad (Journal of Pure and Applied Agriculture, 2023)
This study was performed to evaluate the pre-harvest foliar application of calcium chloride on two grapes varieties ―perlette and king‘s ruby‖. It was confirmed that calcium chloride improved long term storage and berry quality of these grapes varieties. Abstract: Grapes being the most perishable fruit crop need certain pre-harvest measures to improve berry quality. Therefore, current study was conducted for the improvement of early bearing ‗Perlette‘ and ‗King‘s Ruby‘ table grape cultivars by applying pre-harvest sprays of calcium chloride (CaCl2) concentrations. Table grape cvs. ‗Perlette‘ and ‗King‘s Ruby‘ were sprayed at 15 days‘ interval from fruit set to maturity with different concentrations of CaCl2 (0, 0.5%, 0.75% and 1.0%) to evaluate the photosynthetic activity and postharvest biochemical quality. Pre-harvest sprays of 0.5% and 0.75% maintained increased net photosynthetic rate (A) in ‗King‘s Ruby‘ and ‗Perlette‘ respectively; whereas transpiration rate (E) and stomatal conductance (gs) was significantly higher with 0.75% treatment in both cultivars. Pre-harvest foliar sprays of 0.5% and 0.75% CaCl2 significantly improved berry quality with increased berry length and diameter. Postharvest biochemical quality of ‗Perlette‘ and ‗King‘s Ruby‘ was considerably improved with higher TSS, TA, ascorbic acid contents, sugars, total phenolic contents and antioxidants. These results clearly depicted that pre-harvest application of different CaCl2 concentrations improved growth, development, physico-chemical and antioxidative attributes of table grape cvs. ‗Perlette‘ and ‗King‘s Ruby‘ under long term storage conditions at 0.5 ± 0.5 °C and 90 % RH for four weeks. © 2020 Department of Agricultural Sciences, AIOU